Lark ascending : a novel - House, Silas, 1971- (Algonquin Books of Chapel Hill, 2022)
In the near future, as fires devastate most of the United States, Lark and his family secure a place on a boat headed to Ireland, which is rumored to be accepting refugees and is the last country not yet overrun by extremists.